Emergency responders' perceptions of Hydrogen Fuel Cell Vehicle: A qualitative study on the U.K. fire and rescue services. (21st September 2021) - Li, Hanlin; Welsh, Ruth; Morris, Andrew
Abstract: Due to the fast growth of the Hydrogen Fuel Cell Vehicle (HFCV) market, the chances of these vehicles being involved in road crashes is also likely to increase. However, to date, studies into the Emergency Responders' perceptions of the HFCV have been limited. This paper investigates such perceptions of HFCVs through the interviews with firefighters. Through a pilot study results, initial findings suggest that firefighters are the ones who work next to the HFCV in post-crash scenarios, hence, they can provide more insightful information. As a result, 19 themes regarding their perceptions were discovered. The results show that the firefighters have different perceptions of the HFCV regarding the "economic cost". Further analysis indicates the contradictions in their perceptions, and also shows they had more concerns about rescue-oriented safety rather than the fire-oriented safety. Finally, recommendations to address these concerns are discussed as well as the political implications of the results. Highlights: Emergency Responder's perception of the HFCV has been revealed. Fire and Rescue Service (FRS) is the core when dealing with the HFCV incidents. The FRS interprets the economic cost in terms of the local business continuity. Contradictions occur in their perception, which caused by their knowledge level. More concerns about rescue-oriented safety rather than the fire-oriented safety.